Biology essentials for dummies - Kratz, René Fester; Siegfried, Donna Rae.; Cumbay, Medhane; Cumbay, Traci (Hoboken, NJ : Wiley, 2011)
Focuses on the core concepts you need to succeed in an introductory biology course.
Exploring the living world -- The chemistry of life -- The living cell -- Energy and organisms -- Reproducing cells -- DNA and proteins: life partners -- Ecosystems and populations -- Understanding genetics -- Biological evolution -- Ten great biology discoveries.
Includes index.
Keywords: Biology